Pancasila as the Basic Values ​​in Science and Technology Development Strategy in Indonesia - Azidan, M. Fazrel; Naufal, M. Fauzan; Ramadhian, Satria; Zulkarnain, Fahmi; Frans Hutapea, Rangga; Pradana Zale, Havizh; Amri, Afnan (Borneo Novelty Publishing, 2025)
Purpose -This study aims to explore the application of Pancasila values ​​in the context of the development of science and technology in Indonesia. The main focus is how Pancasila can be a philosophical foundation as well as an ethical guideline in directing innovation and technological progress in accordance with the character of the nation.Research Methodology / Design / Approach -The method used in this study is a literature review. This approach involves analyzing various sources that discuss the relationship between Pancasila values ​​and the development of science and technology in Indonesia.Findings -The results of the analysis show that Pancasila not only functions as a philosophical basis but also as an ethical guide in innovation and technological development. Values ​​such as social justice, unity, and just and civilized humanity are important criteria in determining the direction and impact of technological development.Originality / Value- This study emphasizes the importance of integrating Pancasila values ​​at every stage of the development of science and technology in order to align with the needs of society and the character of the Indonesian nation. These findings provide a strategic contribution for policy makers and innovators to prioritize moral and social aspects in technological progress.